Immediate Effect of Vertibrace Dynamic Orthosis on Gross Motor Function in a Child with Spastic Cerebral Palsy: A Case Study - Alaa Noureldeen Kora; Faten Hassan Abdelazeim (BioScientific Review, 2019)
Children with spastic cerebral palsy usually display a decline in their gross motor functional abilities as compared to their peers of the same chronological age. Orthosis has been used widely to manage spasticity, prevent contractures, maintain the range of motion and improve motor function. The purpose of the study was to see the immediate effect of Vertibrace Dynamic Ankle Foot Orthosis on gross motor function abilities of a child with spastic cerebral palsy. A child with spastic cerebral palsy level I on gross motor function classification system was selected to wear the Vertibrace Dynamic Ankle Foot Orthosis. Gross motor abilities were assessed before and after wearing the orthosis using the gross motor function measure. Vertibrace Dynamic Ankle Foot Orthosis showed an immediate improvement in the gross motor abilities by 3% in the child with spastic cerebral palsy with regard to kneeling, walking, running and jumping. Hence, Vertibrace Dynamic Orthosis can be prescribed for enhancement of gross motor abilities in children with spastic cerebral palsy. Further randomized control research about the effects of Vertibrace Dynamic Ankle Foot Orthosis is recommended by assessing a larger number of subjects and evaluating different variables.